SAE International's dictionary for automotive engineers - Kershaw, John F. (SAE International, 2023)
Without vision you may not succeed, so the vision for SAE International's Dictionary of Automotive Engineering is to become the most comprehensive automotive engineering reference for professionals and students alike. This authoritative reference provides clearly written, easy-to-understand definitions for over 1,800 terms used in automotive engineering worldwide. Unlike a standard dictionary that provides only definitions, the SAE International's Dictionary for Automotive Engineers provides a unique level of details including: In-depth definitions including formulas and equations where appropriate. Over 300 full-color illustrations to provide clarity for a definition, component, or system identification. References to relevant SAE Standards to direct the read to additional information beyond a practical definition. Coverage of newer technologies such as electric vehicles, automated vehicles, hydrogen fuel. Organized in alphabetical order, readers will find most acronyms are listed first followed by the term then the definition to mimic conventional usage of acronyms within the industry. Whether you use the print or eBook addition, SAE International's Dictionary of Automotive Engineering exceeds similar resources providing readers with comprehensive view of all SAE offers by providing SAE Standard Identification whenever appropriate.